A new variant of the Friedlander reaction in the synthesis of 7,8-dihydro-6H-furo[2,3-b] quinolin-5-ones - Zotova, Irina Sergeevna; Куличихина , Яна Юрьевна; Ковыгин, Юрий Александрвич (Известия Саратовского университета. Новая серия: Серия Химия. Биология. Экология)
Hydrogenated derivatives of acridine exhibit various types of biological activity – their antibacterial, antitumor, antiviral, psychoactive properties are known. Using the example of heteroanalogs of tacrine, a known cholinesterase inhibitor, it is shown that the replacement of the benzene ring in polycyclic systems with a fi ve-membered heterocycle leads to a decrease in the toxicity of the drug, but does not change the basic physiological activity. Thus, the synthesis of heteroanalogs of known benzannelated systems is an urgent task. This work is devoted to the development of eff ective approaches to the synthesis of some new furotetrahydroquinolines based on the condensation of 2-amino-3-cyanofurans with carbonyl compounds. A promising modifi cation of the Friedlander reaction is proposed, which involves the use of preparatively available cyclohexane-1,3-diones as a substrate. A two-step one-pot method for the synthesis of furoquinoline-5-ones is developed, suitable for precursors sensitive to acids. It was found that the interaction of 2-amino-3-cyano-5-arylfuran with 5-aryl- and 5-hetarylcyclohexane-1,3-diones under tin tetrachloride catalysis leads to the formation of 2-aryl-4-amino-7,8-dihydro-6H-furo[2,3-b]quinolin5-ones. The products are formed in medium yields (50–60%). It has been established that under the conditions of recording NMR spectra (DMSO-d6, 300K), the compounds exist in the tautomeric form of 4-imino-2,7-diaryl-6,7,8,9-tetrahydrofuro[2,3-b]quinolin-5-one. It has been shown that heating 2-amino-3-cyano-5-arylfurans with substituted cyclohexane-1,3-diones in toluene with azeotropic distillation of water in the presence of toluenesulfonic acid formed the corresponding Schiff bases, which cyclized only upon heating with tin tetrachloride. It has been established that during the interaction of 2-amino-3-cyano-5-arylfuran with camphor, both under catalysis by toluenesulfonic acid and in the presence of tin chloride, condensation of the intermediate into the expected 8,10,10-trimethyl-2-aryl-5,6,7,8-tetrahydro-5,8- methanofuro[2,3-b]quinoline-4-amine did not occur. The composition and structure of the synthesized compounds has been confi rmed using IR and NMR-1H spectroscopy.